Faktor-faktor yang Memengaruhi Deviden Payout di Bursa Efek Indonesia - Meiharriko; Achsani, Noer Azam; Santoso, Moch. Hadi (School of Business, Bogor Agricultural University (SB-IPB), 2022)
The Dividend policy is an important information that investors shall know before investing in a stock market. In this study, an analysis of dividend policy is carried out involving the variables lagged dividend, profitability, growth, liquidity, debt, company size, ownership of BUMN and changes in the leadership towards the dividend payout ratio (DPR). The intention of this research are to analyze the variables that affect the DPR in Indonesia Stock Exchange (IDX), in each industrial sector and impact of changes in leadership on the dividend payout ratio within period 2010–2019. The purposive sampling method is applied in data preparation and there are 231 companies paid dividends during the periods. Dynamic panel data regression is practically applied in analysing data to get the conclusion of this research. The results find variables lagged dividend and profitability are significant and positively correlating on the period 2010– 2019. Result in each industrial sector find variable lagged dividend is significant in almost in all industrial sectors. Variable of the lagged dividend is also significant for both periods of the leadership but profitability and growth only significant in the period of 2015 - 2019. Meanwhile, changes in leadership does not has impact towards dividend payout ratio in Indonesia. This research provides additional empirical evidence that explains the dividend policy in Indonesia is following the dividend smoothing theory Keywords: DPR, IDX, industry, lagged dividend, profitability